The Urgency of Developing an Integrated Multimodal Educational Pragmatics Textbook - Nanda Permatasari, Agmi Sinta; Rahardi, R. Kunjana; Setyaningsih, Yuliana (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to describe the urgency of developing educational pragmatics textbooks integrated with multimodality. This research uses mixed-method research. The subjects of this research are students, alumni, and documents in the form of semester learning plans for educational pragmatics courses. The data obtained were the results of filling out questionnaires and the results of document analysis. The data collection techniques used were questionnaires and literature studies. This research uses qualitative and quantitative methods to analyze the data obtained. Questionnaire data were analyzed using qualitative and quantitative, while the results of document analysis were analyzed using qualitative. Based on the research, the researcher found that 62% of students and alumni had difficulty understanding educational pragmatics. To help students there are already several books that help, such as educational pragmatics textbooks and reference books. However, these books have not been integrated with multimodality, so students still have difficulty understanding educational pragmatics. Therefore, educational pragmatics teaching materials that are integrated with multimodality are needed. This is supported by the questionnaire given that 97% of students and alumni strongly agree that the development of multimodality integrated educational pragmatics textbooks in learning for students is important and urgent. With the multimodality-based educational pragmatics textbook, students find it easier to understand educational pragmatics.